Peningkatan Hasil Belajar dan Sikap Percaya Diri Siswa melalui Model PjBL pada Siswa Kelas IV SD - Jodhipati, Muhammad; Sayekti, Ika Candra; Tasmun, Tasmun (FONDATIA, 2024)
This research aims to enhance students' learning outcomes and self-confidence in Pancasila Education through the implementation of the Project Based Learning model in class 4D at SDN Kleco 1 Surakarta. The Action Research method is employed, consisting of two cycles: planning, action, observation, and reflection. Data collection involves observation, tests, and documentation, utilizing instruments such as test questions, observation sheets, and photo documentation. Data are analyzed descriptively comparatively and validated through triangulation. Learning outcome indicators focus on the cognitive domain, while self-confidence indicators include asking questions, acting without hesitation, trying new things, participating, and feeling comfortable. The research involves 21 students in class 4D. The results indicate an improvement in learning outcomes, from 7 to 18 students achieving competency, and an increase in self-confidence, from 7 to 30 students scoring 4 out of 5 aspects. In conclusion, the implementation of Project Based Learning effectively enhances students' learning outcomes and self-confidence in Pancasila Education.